Investor attention and portfolio performance : what information does it pay to pay attention to? - Davydov, Denis; Khrashchevskyi, Ian; Peltomäki, Jarkko (Routledge, 2021)
We explore a unique dataset on individual investors’ online trading accounts to examine the determinants of their attention and its relation to portfolio performance. In particular, we investigate what individual characteristics affect investor attention and what type of information drives investment performance. We find distinct differences in investors’ attention and provide evidence that paying attention has a differential impact on performance depending on the type of information. Portfolio monitoring and attention to financial education are positively related to performance, while attention to analytical information is detrimental to performance. Attention to technical analysis is negatively related to the performance of actively trading investors but improves the performance of less frequent traders. Overall, our results provide additional evidence to the suggestion that attention to financial education is the key to investment success.
Keywords: financial education; information type; investor attention; portfolio performance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|